Laser-induced graphene electrochemical sensor for quantitative detection of phytotoxic aluminum ions (Al3+) in soils extracts - Reyes-Loaiza, Vanessa; De La Roche, Jhonattan; Hernandez-Renjifo, Erick; Idárraga, Orlando; Silva, Mayesse Aparecida da; Valencia, Drochss P.; Ghneim-Herrera, Thaura; Jaramillo-Botero, Andres (Nature Portfolio, 2024)
Aluminum in its Al 3+ form is a metal that inhibits plant growth, especially in acidic soils (pH < 5.5). Rapid and accurate quantitative detection of Al 3+ in agricultural soils is critical for the timely implementation of remediation strategies. However, detecting metal ions requires time-consuming preparation of samples, using expensive instrumentation and non-portable spectroscopic techniques. As an alternative, electrochemical sensors offer a cost-effective and minimally invasive approach for in situ quantification of metal ions. Here, we developed and validated an electrochemical sensor based on bismuth-modified laser-induced graphene (LIG) electrodes for Al 3+ quantitative detection in a range relevant to agriculture (1–300 ppm). Our results show a linear Al 3+ detection range of 1.07–300 ppm with a variation coefficient of 5.3%, even in the presence of other metal ions (Pb 2+ , Cd 2+ , and Cu 2+ ). The sensor offers a limit of detection (LOD) of 0.34 ppm and a limit of quantification (LOQ) of 1.07 ppm. We compared its accuracy for soil samples with pH < 4.8 to within 89–98% of spectroscopic methods (ICP-OES) and potentiometric titration. This technology's portability, easy to use, and cost-effectiveness make it a promising candidate for in situ quantification and remediation of Al 3+ in agricultural soils and other complex matrices.